Survival after high-dose chemotherapy for refractory and recurrent Ewing sarcoma. (July 2022) - Windsor, Rachael; Hamilton, Anthony; McTiernan, Anne; Dileo, Palma; Michelagnoli, Maria; Seddon, Beatrice; Strauss, Sandra J.; Whelan, Jeremy
Abstract: Background: outcome of primary refractory or recurrent Ewing sarcoma (RRES) is poor and the role of high-dose therapy (HDT) remains uncertain. We retrospectively reviewed all patients treated for RRES in the London Sarcoma Service (LSS) over a 22-year period with the aim of adding to the current literature and developing a prognostic risk score to aid clinical decision-making. Methods and results: One hundred and ninety-six patients were included; 64 patients received HDT, 98 standard non-HDT chemotherapy and 34 no systemic therapy. At RRES, median age was 20 years and seventy-four per cent of patients had progressed or relapsed within 24 months. Median overall survival for HDT and non-HDT patients was 76 months (95% CI 34.8–117.2) and 10.5 months (95% CI 8.9–12.1), respectively. Two and five-year post-relapse survival (PRS) for HDT patients was 67.9% (SE 5.9) and 52.7% (SE 6.5), and for non-HDT patients, 20.5% (SE 4.2) and 2% (SE 1.5). Four prognostic factors significant on multivariate analysis were assigned a score of one point each, creating good (score 0), intermediate (score 1–2) and poor (score 3–4) prognosis groups. The increased score was significantly associated with reduced PRS. Conclusion: Our study demonstrates that in RRES, HDT is associated with superior outcomes compared with non-HDT chemotherapy. RRES patients can be risk-stratified according to a predictive prognostic index we have developed, with the potential benefit of HDT observed even in patients with poor prognostic scores. Highlights: Ewing sarcoma is a malignant bone tumour with a predilection for young people. Refractory or recurrent disease has a dismal prognosis. High-dose chemotherapy and autologous stem-cell transplant may prolong survival. Risk stratification at relapse may aid clinical decision-making.